2017
DOI: 10.1186/s13063-017-1801-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of high-intensity focused ultrasound-assisted hepatic resection (HIFU-AR) on blood loss reduction in patients with liver metastases requiring hepatectomy: study protocol for a randomized controlled trial

Abstract: BackgroundLiver resection is the only potentially curative treatment for colorectal liver metastases (LM). It is considered a safe procedure, but is often associated with blood loss during liver transection. Blood transfusions are frequently needed, but they are associated with increased morbidity and risk of recurrence. Many surgical devices have been developed to decrease blood loss. However, none of them has proven superior to the standard crushing technique. We developed a new, powerful intra-operative hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
(21 reference statements)
0
7
0
Order By: Relevance
“…Most reports on clinical use of HIFU in liver tumor treatment are from China where USgHIFU has been used for HCC treatment, with reports of adequate feasibility, safety, and treatment outcomes (121)(122)(123)(124). In Europe, a current study examines the role of HIFU in reducing blood loss during liver resection (125). Only one single case of clinical treatment in liver tumors is reported from Europe (Rome) using MRgHIFU (126), and MRgHIFU is not in clinical use in treatment of liver tumors yet.…”
Section: High Intensity Focused Ultrasoundmentioning
confidence: 99%
“…Most reports on clinical use of HIFU in liver tumor treatment are from China where USgHIFU has been used for HCC treatment, with reports of adequate feasibility, safety, and treatment outcomes (121)(122)(123)(124). In Europe, a current study examines the role of HIFU in reducing blood loss during liver resection (125). Only one single case of clinical treatment in liver tumors is reported from Europe (Rome) using MRgHIFU (126), and MRgHIFU is not in clinical use in treatment of liver tumors yet.…”
Section: High Intensity Focused Ultrasoundmentioning
confidence: 99%
“…There was no obvious difference in the 6-month (OR =9.03, 95% CI: 0.87, 94.13, P=0.07) or 3-year (OR =2.26, 95% CI: 0.46, 11.21, P=0.32) SRs of patients between the 2 groups (P>0.05). The included articles showed homogeneity in the SRs of patients at 1 year, 2 years, and 5 years after surgery (I 2 <50%; Figures 5,6,8), so a fixed-effect model (FEM) was adopted. The SRs of patients in the experimental group at 1 year (OR =3.13, 95% CI: 1.92, 5.11, P<0.00001), 2 years (OR =3.38, 95% CI: 1.71, 6.66, P=0.0004), and 5 years (OR =2.15, 95% CI: 1.02, 4.55, P=0.04) after surgery were observably better than those of patients in the control group, and the differences were statistically significant (P<0.05).…”
Section: Effect Of Hifu + Tace On Postoperative Sr Of Patients With Lcmentioning
confidence: 99%
“…In recent years, high-intensity focused ultrasound (HIFU) has been used as a tumor treatment method. Ultrasound can be used to achieve precise localization of the tumor lesions and deliver subsequent thermal tumor ablation therapy ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Results have been reported using the device for ablating tissue near tumors in segments prior to surgical resection, to assess accuracy and safety. Applications include reduction of hemorrhaging during surgery and potentially bridging more patients for surgical resection [190][191][192][193]. The device was shown capable of in vivo hepatic vessel occlusion for diameters of 2 mm [194], and studies have reported diameters of left hepatic arteries and right hepatic veins between 3 and 4 mm [195].…”
Section: Focused Ultrasound Clinical Studies For Liver Cancermentioning
confidence: 99%